Intelligence and strategic culture - Duyvesteyn, Isabelle ([S.l.] : Routledge, 2012)
Reliable information on potential security threats is not just the result of diligent intelligence work but also a product of context and culture. The volume explores the nexus between the intelligence process and strategic culture. How can and does the strategic outlook of the United States and the United Kingdom in particular, influence the intelligence gathering, assessment and dissemination process? This book contains an assessment of how political agendas and ideological outlook have significant influence on both the content and process of intelligence. It looks in particular at the premise of hearts and minds policies, culture and intelligence gathering in counterinsurgency operations; at case studies from imperial Malaya and Iran in the 1950s and at instances of intelligence failure, e.g. the case of Iraq in 2003. How was intelligence, or the lack thereof, a product of political culture and how did it play a role in the political praxis? The book shows that political agendas and the ideological outlook have a significant influence upon both the content and process of intelligence. This book was originally published as a special issue of Intelligence and National Security .
Keywords: Great Britain; Intelligence service; Political science--Decision making; Strategic culture; United States